2019
DOI: 10.1007/s40789-019-00274-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of a vitrinite-rich and an inertinite-rich Witbank coal (South Africa) using pyrolysis-gas chromatography

Abstract: This study aims to compare iso-rank vitrinite-rich and inertinite-rich coal samples to understand the impact of coal-forming processes on pyrolysis chemistry. A medium rank C bituminous coal was density-fractionated to create a vitrinite-rich and an inertinite-rich sub-sample. The vitrinite-rich sample has 83 vol% total vitrinite (mineral-matter-free basis), whereas the inertinite-rich counterpart has 66 vol% total inertinite. The vitrinite-rich sample is dominated by collotelinite and collodetrinite. Fusinite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 54 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…In addition to the physical structure, the chemical structures of the maceral groups are also different. 13 C nuclear magnetic resonance (NMR) is widely used in the characterization of the carbon skeleton structure of fossil fuels (Moroeng et al, 2019;Ping et al, 2020), which can give the chemical structure of coal. Ping et al (2021) analyzed the chemical structure of subbituminous coal by 13 C NMR and concluded that vitrinite has more side chains of aliphatic hydrocarbons than inertinite, while inertinite has more aromatic rings and more oxygen-aliphatic structures than vitrinite.…”
Section: Structural Differencementioning
confidence: 99%
“…In addition to the physical structure, the chemical structures of the maceral groups are also different. 13 C nuclear magnetic resonance (NMR) is widely used in the characterization of the carbon skeleton structure of fossil fuels (Moroeng et al, 2019;Ping et al, 2020), which can give the chemical structure of coal. Ping et al (2021) analyzed the chemical structure of subbituminous coal by 13 C NMR and concluded that vitrinite has more side chains of aliphatic hydrocarbons than inertinite, while inertinite has more aromatic rings and more oxygen-aliphatic structures than vitrinite.…”
Section: Structural Differencementioning
confidence: 99%